Gastronomic identity in the novel Francesca e Nunziata - Bona, Fabiano Dalla (Revista de Letras, 2014)
Where can identity be found? If people’s identity can be built through their language, the same phenomenom can also be seen through literature and gastronomy. The multiple connections between gastronomy/food and identity are present in literature, specifically Italian literature, from antiquity to the present day. This article investigates these relationships trough the novel Francesca e Nunziata, of the Italian writer Maria Orsini Natale (2001), in light of Hall’s (1996), Ciampa’s and Castells’ (1990, 1999) theoretical postulates, and Italians like Montanari (2002), Teti (1999)and Saban and Serventi (2004). The novel is a novel where things triumph over people and these things are strong markers in a regional and/or national identity level.